Is there a consistent association between coronary heart disease and ischemic stroke caused by intracranial atherosclerosis? - Adriana B. Conforto; Claudia da Costa Leite; Cesar H. Nomura; Edson Bor-Seng-Shu; Raul D. Santos (Arquivos de Neuro-Psiquiatria)
Coronary heart disease and ischemic stroke are frequent coexistent conditions that share risk factors and pose major burdens to global health. Even though a clear relation has been established between extracranial internal carotid artery atherosclerosis and symptomatic or asymptomatic coronary heart disease, there is a gap in knowledge about the association between intracranial atherosclerosis and coronary heart disease. Intracranial atherosclerosis is associated with high risks of stroke recurrence and vascular death. More research and clinical trials are needed to answer whether early diagnosis of asymptomatic coronary heart disease and aggressive treatment can decrease the risk of vascular death in patients with ischemic stroke caused by intracranial atherosclerosis.